2021
DOI: 10.3390/genes12122024
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Cortical Thickness in Adolescents with Autism Spectrum Disorder and Their Association with Restricted and Repetitive Behaviors

Abstract: The neuroanatomy of autism spectrum disorder (ASD) shows highly heterogeneous developmental trajectories across individuals. Mapping atypical brain development onto clinical phenotypes, and establishing their molecular underpinnings, is therefore crucial for patient stratification and subtyping. In this longitudinal study we examined intra- and inter-individual differences in the developmental trajectory of cortical thickness (CT) in childhood and adolescence, and their genomic underpinnings, in 33 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 71 publications
(126 reference statements)
4
10
0
Order By: Relevance
“…Stereotyped behaviors, ritualistic behaviors, and restricted behaviors improved greatly after childhood. These finding corroborated previous studies that reported a broad range of trajectories of RRBIs in ASD patients (8)(9)(10)24). For children, RRBIs are relatively stable between 2 and 7 years of age (9).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Stereotyped behaviors, ritualistic behaviors, and restricted behaviors improved greatly after childhood. These finding corroborated previous studies that reported a broad range of trajectories of RRBIs in ASD patients (8)(9)(10)24). For children, RRBIs are relatively stable between 2 and 7 years of age (9).…”
Section: Discussionsupporting
confidence: 91%
“…We found that significant reductions of FC among brain regions in the temporal lobe, occipital lobe, and cingulate might contribute to the trajectory of RRBIs over time, especially stereotyped behaviors and overall RRBIs (evaluated by the RBSR-6). Previous studies that examined associations between cortical thickness and RRBI severity over time found that gray matter thickness of the orbital frontal cortex and middle frontal cortex correlated with self-injurious behaviors in adolescent patients (24). In the present study, core brain regions that were responsible for stereotyped behaviors included the superior occipital gyrus, insula, rolandic operculum, angular, caudate, and cingulum.…”
Section: Discussionsupporting
confidence: 48%
“…For example, the role of mutations in the mTOR or RAS signalling pathways show similar neuropathological characteristics in human and rodent models [ 16 ]. Gene expression pattern, neural synaptic function, or the imbalance of inhibitory and excitatory neural functions are other well-studied aspects which can be compared between rodent and human models [ 13 , 17 , 18 ]. Additionally, the role of somatic mutations has been the focus of recent exciting developments, especially in the field of treatment-resistant epilepsy, as documented both in humans and in animal models [ 19 , 20 ].…”
Section: Joint Mechanisms Across Modelsmentioning
confidence: 99%
“…For example, Bieneck et al, show that the physiological cortical thinning in individuals with ASD during adolescence was decreased compared to typical controls; this possibly indicates abnormalities in the process of synaptic pruning. Interestingly, the observed differences in cortical thinning correlated with synaptic genes [ 21 ]. These findings echo previous observations, indicating an association between synaptic genes and differences in cortical thickness in individuals with ASD [ 22 , 23 ].…”
mentioning
confidence: 99%
“…These findings echo previous observations, indicating an association between synaptic genes and differences in cortical thickness in individuals with ASD [ 22 , 23 ]. Bieneck et al, reported altered cortical thinning predominantly in fronto-temporal brain regions and the cingulate cortex in individuals with ASD [ 21 ]. In addition, these developmental changes were associated with severity of repetitive behaviors, while the most affected brain regions were enriched for genes involved in synaptic function, corroborating earlier studies indicating the involvement of synaptic genes in cortical thickness [ 22 ].…”
mentioning
confidence: 99%